Influence of basketball shoe midsole inserts featuring different mechanical rebound properties on biomechanical loading and subjective perception during a side-cutting maneuver - Pan, J. W.; Sterzing, T.; Pang, J. W.; Chua, Y. K.; Kong, P. W. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
This study examined the influence of basketball shoe midsole inserts with different forefoot and rearfoot rebound properties on biomechanical loading and subjective perception during a side-cutting maneuver. Eleven male basketball players executed side cutting in four shoe conditions mechanically characterized for their rearfoot/forefoot rebound: compliant/compliant, springy/springy, compliant/springy, and springy/compliant. Lower extremity kinetics and kinematics (normalized to body mass), as well as subjective perception, were measured. During the weight-acceptance phase, there were no differences between shoes in all biomechanical variables, except a slightly greater ankle range of motion (1.2° greater than the other three shoes) in the frontal plane for shoe compliant/springy. During the push-off phase, shoe springy/springy led to a greater ankle plantarflexion moment (1.21 Nm/kg greater than the other three shoes, p < 0.001) and knee internal rotation moment (0.09 Nm/kg greater than the other three shoes, p = 0.012), while shoe compliant/springy resulted in a greater ankle range of motion in the frontal plane (1.4° greater than the other three shoes, p < 0.001). Perception data showed no statistically significant difference among any shoes. In conclusion, springy inserts of basketball shoe midsoles induced a biomechanical loading effect. Perception of players being unaffected indicates the importance of biomechanical evaluation to examine the effects of the given shoe modifications during side cutting.